PENGARUH HUTANG TERHADAP PROFITABILITAS PADA PT. PERKEBUNAN NUSANTARA VI TAHUN 2018–2021 - Ferdyan Wana Saputra; Muhammad Azrafeno; Niken Ayuningrum; Johandri Iqbal (Journal of Applied Accounting And Business, 2023)
This research was conducted at PT. Perkebunan Nusantara VI. The purpose of this study is to determine whether debt, both long-term debt and short-term debt has a significant effect on profitability, which in this study is represented by the Net Profit Margin Ratio (NPM). The research period is 2018-2021. The problem formulation of this study aims to determine how significant the influence of long-term debt and short-term debt on profitability at PT. Perkebunan Nusantara VI. This research is a quantitative research. With the type of data used is secondary data obtained in the financial statements of PT. Perkebunan Nusantara VI . The data analysis technique used in this study is multiple linear regression analysis using the SPSS version 26.0 program with the regression equation Y = -0.018 - 0.064X1 + 0.133X2. Based on the results of tests conducted on SPSS, it is found that there is no significant effect between long-term debt on profitability. Meanwhile, for short-term debt, it can be concluded that there is no significant effect between short-term debt on profitability. In the F test or simultaneous test, it is concluded that there is no significant effect between long-term debt and short-term debt on profitability simultaneously. Adjusted R2 value of 14.6% coefficient indicates that the profitability variable can be explained by long-term debt and short-term debt. While the remaining 85.4% is influenced by other variables that are not explained in this research model.